2023
DOI: 10.1038/s41598-023-33979-2
|View full text |Cite|
|
Sign up to set email alerts
|

Psychopharmacological treatment of disruptive behavior in youths: systematic review and network meta-analysis

Abstract: To conduct a systematic review of the comparative efficacy of various psychotropic medications for the treatment of disruptive behavior (DBs) in youths. To this aim, we systematically reviewed randomized clinical trials (RCTs) of various psychotropic medications targeting symptoms of DBs and applied network meta-analysis to investigate their relative efficacy. Fifty-five RCTs meeting the inclusion criteria were selected. To predict and interpret relative treatment efficacy, we compared the efficacy of various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 139 publications
0
3
0
Order By: Relevance
“…Efficacy-oriented systematic reviews, such as that conducted by de Pablo et al (2023), agree that risperidone and aripiprazole are efficacious as interventions for irritability and emotional dysregulation but, despite this, researchers emphasise that these medications can only comprise one element of a multicomponent intervention and are best prescribed for only short-term usage. Seok et al (2023) conducted a network meta-analysis of randomised control trials of the comparative efficacy of psychotropic medications prescribed to treat disruptive behaviour in young people (diagnoses included autism, ADHD, conduct disorder, disruptive behaviour disorder) and found that second-generation psychotropic medications with greater dopaminergic receptor affinity (e.g., risperidone) showed significant efficacy in reducing disruptive behaviour (Seok et al, 2023).…”
Section: Psychopharmacological Treatmentsmentioning
confidence: 99%
“…Efficacy-oriented systematic reviews, such as that conducted by de Pablo et al (2023), agree that risperidone and aripiprazole are efficacious as interventions for irritability and emotional dysregulation but, despite this, researchers emphasise that these medications can only comprise one element of a multicomponent intervention and are best prescribed for only short-term usage. Seok et al (2023) conducted a network meta-analysis of randomised control trials of the comparative efficacy of psychotropic medications prescribed to treat disruptive behaviour in young people (diagnoses included autism, ADHD, conduct disorder, disruptive behaviour disorder) and found that second-generation psychotropic medications with greater dopaminergic receptor affinity (e.g., risperidone) showed significant efficacy in reducing disruptive behaviour (Seok et al, 2023).…”
Section: Psychopharmacological Treatmentsmentioning
confidence: 99%
“…Because psychotherapeutic interventions for excessive anger are helpful but do not work for everyone, appropriate physiological treatments can be brought to bear. Seok et al’s (2023) recent meta-analysis found that second generation antipsychotics like respiridol were more efficacious than stimulant and other medications in reducing angry aggression in youth. There are no comparative data on these agents for adults in whom clinically significant but milder outbursts can be controlled with the specific serotonin re-uptake inhibitor fluoxetine (R.…”
Section: Treatment Of Excessive Anger and Reactive Aggression: Psycho...mentioning
confidence: 99%
“…Because psychotherapeutic interventions for excessive anger are helpful but do not work for everyone, appropriate physiological treatments can be brought to bear. Seok et al's (2023) recent metaanalysis found that second generation antipsychotics like respiridol were more efficacious than stimulant and other medications in This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Treatment Of Excessive Anger and Reactive Aggression: Psycho...mentioning
confidence: 99%